PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT BANK MANDIRI AREA MEDAN IMAM BONJOL - Siregar, Indah Permatasari; Nasution, Ananda Anugrah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2021)
This research aimed to know the effect of organizational culture and individual characteristics to performance with intrinsic motivation as intervening variable in the Employee Marketing Division of PT. Bank Mandiri Persero Tbk Medan Imam Bonjol II. Population in this research is all employees of marketing division of PT. Bank Mandiri (Persero), Tbk Imam Bonjol Medan Area which amounted to 50 people. Sampling using sampling saturated, where all the population used as a sample. The method of analysis used in this study is quantitative descriptive method and the nature of this study using the level of associative explanation and analysis techniques used the regression analysis. The result of the research shows that independent variables, organizational culture have a significant and significant effect on the performance of PT. Bank Mandiri Persero Tbk Medan Imam Bonjol II Area with determination coefficient of 0,567 or 56,7%. Partially organizational culture, individual characteristics, and intrinsic motivation, simultaneously have a significant and positive effect on performance